2003
DOI: 10.1074/jbc.m305390200
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Structural Domains Required for Neural Cell Adhesion Molecule Polysialylation by PST/ST8Sia IV and STX/ST8Sia II

Abstract: A limited number of mammalian proteins are modified by polysialic acid, with the neural cell adhesion molecule (NCAM) being the most abundant of these. We hypothesize that polysialylation is a protein-specific glycosylation event and that an initial protein-protein interaction between polysialyltransferases and glycoprotein substrates mediates this specificity. To evaluate the regions of NCAM required for recognition and polysialylation by PST/ST8Sia IV and STX/ST8Sia II, a series of domain deletion proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 73 publications
5
63
0
Order By: Relevance
“…The Ig5FN1 module of NCAM is a well-characterized target for polysialylation (27). Thus, this module was used as a reporter for in planta polysialylation.…”
Section: Human Polysialyltransferases Are Functional When Transientlymentioning
confidence: 99%
“…The Ig5FN1 module of NCAM is a well-characterized target for polysialylation (27). Thus, this module was used as a reporter for in planta polysialylation.…”
Section: Human Polysialyltransferases Are Functional When Transientlymentioning
confidence: 99%
“…1), is polysialylated exclusively on O-glycans (38). We also showed that replacing the acidic patch with either alanine or arginine residues substantially decreases or eliminates NCAM7 polysialylation, although replacing the ␣-helix has no effect (40).…”
Section: Fn1 Qvq Sequence Plays a Role In Polyst Positioning For Ig5 mentioning
confidence: 73%
“…It was first observed on salmonid egg polysialoglycoprotein, PSGP (49), and later found on neuropilin-2, CD36, unidentified proteins in the RBL-1 rat basophilic leukemia cell line, and several NCAM mutants, such as those lacking the FN1 ␣-helix or QVQ sequences, and the truncated NCAM protein NCAM7 (29,30,38,40,50). In addition, we frequently observe a small amount of O-glycan polysialylation in full-length NCAM (see Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using NCAM as a model substrate, we showed that the first fibronectin type III repeat (FN1) is required for the polysialylation of N-glycans in the adjacent immunoglobulin domain (Ig5) (24). A three-residue acidic patch on the surface of the FN1 domain plays a primary role in NCAM recognition, binding, and polysialylation by ST8SiaIV (25,27).…”
Section: Polysialic Acid (Polysia)mentioning
confidence: 99%